Nighttime Blue Lighting and Downward Airflow to Manage Tipburn in Indoor Farm Lettuce - John Ertle; Chieri Kubota (HortScience)
Indoor vertical farms (IFs) have gained popularity in the United States within the last decade. Lettuce is the most frequently produced crop in these systems, but it often suffers from the calcium (Ca) deficiency called tipburn because of poor airflow, which causes low transpiration of young leaves near the meristem. We hypothesized that a low-intensity blue light can open stomata and enhance whole-plant transpiration without increasing the overall plant growth rate. Dim light of blue (B100) or blue/red (B80R20) were applied at a photosynthetic photon flux density of 30 µmol·m−2·s−1 to ‘Klee’ and ‘Rex’ lettuce plants during the nighttime for the final 14 days of the 28 days of growth after transplanting. A leaf gas exchange analysis showed that application of B100 lighting alone increased nighttime leaf conductance by more than 50% and transpiration by 25% over nighttime darkness, while the results of B80R20 treatment were not different from those of the B100 or control treatments. However, increased whole-plant transpiration driven by dim nighttime lighting was ineffective for targeting Ca transport to areas of high tipburn risk, and tipburn severity (percentage of leaves with tipburn) was not reduced at harvest (28 days after transplanting). In a second experiment combining B100 lighting or nighttime darkness with downward vertical airflow (0.4 m·s−1), tipburn was eliminated regardless of nighttime lighting. Nighttime dim lighting seems to be an ineffective strategy, and downward vertical airflow is likely the most practical and effective tipburn prevention mechanism for IFs.